Threshold responses of soil microbial communities and functions to 18O-H2O enrichment - Fangying Qu; Lingrui Qu; Yue Liu; Mike Manefield; Bruce A. Hungate; Ember M. Morrissey; Jian Wang; Yi Yang; Juan Piñeiro; Edith Bai; Chao Wang (Soil Biology and Biochemistry, 2026)

A global meta-analysis of snowpack changes on soil carbon and nitrogen cycling and greenhouse gas fluxes - Junni Wang; Ivano Brunner; Edith Bai; Ziping Liu; Yingtong Zhou; Cunguo Wang; Mai-He Li (Global and Planetary Change, 2026)

Afforestation mitigates soil carbon loss in carbon-poor soils under warming - Wenwen Lv; Hailong Zhang; Yang Liao; Edith Bai; Xinli Chen; Zhenhong Hu; Jianzhao Wu; Jiwei Li; Zhouping Shangguan; Lei Deng (Applied Soil Ecology, 2026)

MAOC capacity and microbial drivers refine soil carbon management in forest plantations - Xiaomiao Ma; Chao Wang; Xu Wang; Ziping Liu; Yimei Wang; Edith Bai (Forest Ecology and Management, 2026)

Microbial turnover mediates nonlinear response of soil N2O and CH4 fluxes to diversity loss - Yuxin Yang; Lingrui Qu; Jing Yu; Xiaoyi Huang; Yue Liu; Fangying Qu; Jian Wang; Tingting Yang; Edith Bai; Chao Wang (Soil Ecology Letters, 2026)

Nonlinear effect of microbial diversity loss on soil carbon flux - Chao Wang; Xiaoyi Huang; Jing Yu; Yue Liu; Fangying Qu; Jian Wang; Xu Wang; Edith Bai (Soil Biology and Biochemistry, 2026)

Coupled Temperature Sensitivity of Microbial Carbon and Nitrogen Use Efficiencies in Forest Soils on a Continental Scale - Yang Zhang; Lingrui Qu; Jian Wang; Yue Liu; Meixia Gao; Xu Wang; Fangying Qu; Edith Bai; Chao Wang (Global Change Biology, 2026)
Microbial carbon and nitrogen use efficiencies (CUE and NUE) are critical regulators of soil carbon and nitrogen cycling, with their temperature sensitivities playing a pivotal role in mediating biogeochemical feedbacks under global warming. However, how the temperature sensitivity ( Q 10 ) of CUE and NUE varies at different temperature ranges and whether their thermal responses are coordinated remains poorly understood. Here, we quantified the Q 10 of CUE and NUE in 55 soil samples collected from a ~4000 km latitudinal forest transect in eastern China. We further identified key drivers that shaped Q 10 variability from climatic, edaphic, and microbial factors. On average, Q 10 was 1.22 ± 0.08 for CUE and 1.46 ± 0.13 for NUE. However, both efficiencies exhibited clear temperature‐interval dependence: the mean Q 10 of CUE declined from 1.47 ± 0.14 at 12°C–20°C to 0.97 ± 0.08 at 20°C–28°C, while the mean Q 10 of NUE decreased from 2.00 ± 0.23 to 0.93 ± 0.09. The Q 10 values of CUE and NUE were strongly correlated across temperature ranges and positively associated with the Q 10 of microbial growth, indicating a coordinated thermal response governed primarily by growth‐based processes. At lower incubation temperature interval (12°C–20°C), variation in the Q 10 of CUE was primarily explained by soil stoichiometry and microbial community attributes, whereas under warmer conditions (20°C–28°C), climatic and edaphic constraints, particularly precipitation and soil N/P ratio, became dominant. Although microbial community attributes consistently explained most of the variance in the Q 10 of NUE, their influence weakened at higher incubation temperatures, paralleling the pattern observed for CUE and indicating a shift from biotic to abiotic control. Overall, these findings highlight that the temperature sensitivities of microbial CUE and NUE are tightly coupled, growth‐mediated, and strongly temperature‐context dependent, providing novel insights for improving predictions of soil carbon‐nitrogen turnover under climate warming.

Deep learning-driven investigation of nanoplastic impacts on soil protist behavior in soil chips - Hanbang Zou; Wei Ying; Paola M. Mafla-Endara; Fredrik Klinghammer; Jingmo Bai; Hanwen Kang; Edith C. Hammer (Environmental Pollution, 2026)

Prof Stephen P. Long, FRS (1950–2025) - Lorenzo Álvarez‐Filip; Edith Bai; Carl J. Bernacchi; Rhea Bruno; Klaus Butterbach‐Bahl; Maria Byrne; I‐Ching Chen; Shaolin Chen; William W. L. Cheung; M. Francesca Cotrufo; Tatenda Dalu; Xiaojuan Feng; et al. (Global Change Biology, 2025)

Impact of biochar addition on water use efficiency, biological nitrogen fixation and growth of understory Acacia leiocalyx and Acacia Disparimma in a suburban native forest of subtropical Australia - Sabah Taresh; Shahla Hosseini Bai; Edith Kichamu-Wachira; Zhihong Xu (Journal of Soils and Sediments, 2025)
Purpose This study evaluated the responses of water use efficiency (WUE), biological nitrogen fixation (BNF) and growth of understory Acacia leiocalyx and A. disparimma to the biochar addition and prescribed burning for 9–22 months in a suburban native forest of subtropical Australia. Materials and methods Foliar and surface soil (0–10 cm) samples were collected from two understory species of acacia ( A. leiocalyx and A. disparimma ) and reference plants ( Eucalyptus psammitica ) shortly before biochar application at 0, 5 and 10 t ha −1 and at 1, 2, 3, 6 and 9 months after biochar application or 22 months after prescribed burning. Soil and plant samples were analysed to determine total carbon (C), total nitrogen (N) and C and N isotope compositions (δ 13 C and δ 15 N). Plant growth was measured in the first 9 months after biochar application. Results and discussion Foliar total N was significantly higher ( P < 0.05) for A. leiocalyx than A. disparimma 9 months after biochar application, while foliar total N was significantly lower at 6 months after biochar application for A. disparimma . There were significant differences ( P < 0.05) in BNF between A. leiocalyx and A. disparimma at all the sampling times. The BNF of A. disparimma was significantly higher at 2 months after biochar application than those of A . leiocalyx , while the lower BNF was found in A. leiocalyx at 3 months after biochar application. The BNF ranged from 52.4 to 78.7% for A. leiocalyx and from 65.0 to 84.2% for A. disparimma at 2 months after biochar application. The WUE, as reflected in foliar δ 13 C, was higher for A. disparimma than that of A. leiocalyx at 1, 2, 3, 6 and 9 months after biochar application. There was a significantly higher plant growth for A. leiocalyx than that of A. disparimma when biochar was applied at 10 t ha −1 , while the lowest height was found in the control without biochar application. Conclusions Biochar application improved foliar total N, BNF and growth of understory acacia species in the first 9 months of biochar application in the suburban native forest of subtropical Australia. Both acacia species showed an improved foliar total N, BNF, δ 13 C and δ 15 N after biochar application at the 3 and 9 months after biochar addition compared with those of the control.

Field performance of three variants of the Willems badge-type passive sampler for determining atmospheric sulphur dioxide concentrations in Shenyang, China - Wei Liu; Longfei Liu; Sulian Li; Zhen Sun; Edith Bai; Yimin Liu (Air Quality, Atmosphere & Health, 2025)

Intensified Aridity Hinders Soil Microbes From Improving Their Nitrogen Use Efficiency - Jingyi Yang; Zitong Wang; Ziping Liu; Qing Chang; Bo Wang; Yangjian Zhang; Edith Bai (Global Change Biology, 2025)
Microbial nitrogen (N) use efficiency (NUE) is crucial for retaining N in soils and supplying N to plants. However, how soil microbial NUE in N‐limited dryland responds to aridity remains poorly understood. Here we used 18 O and 15 N isotope labeling techniques to investigate the effects of climatic, edaphic, and biotic factors on microbial N metabolism along a 2200 km aridity gradient on the Tibetan Plateau. We found soil microbes could enhance their NUE to cope with N limitation, but this ability was hindered when aridity index (AI) 0.12), microbes increased their NUE with decreasing aridity because they got more limited by N and temperature. The increase of microbial NUE increased microbial necromass N, contributing to the increase of soil total N. Our findings provide new insights into microbial N use strategies under water‐ and N‐limited conditions and their vital role in N retention in ecosystems. This helps to deploy microbial potential in conserving N in soils for higher productivity and to better predict soil N processes under global changes.

Refining Amino Sugar‐Based Conversion Factors for Quantification of Microbial Necromass Carbon in Soils - Di Meng; Kun Zhang; Ziping Liu; Yongxin Zang; Shasha Liu; Jingyi Yang; Edith Bai (Global Change Biology, 2025)
Quantifying the contribution of microbial necromass to soil organic carbon (SOC) has been a hot topic in the past decade, offering critical insights into soil carbon sequestration mechanisms. Amino sugars (AS) are widely used biomarkers for estimating microbial necromass in soils, with the ratios of AS to microbial necromass carbon (MNC) serving as conversion factors to derive MNC from AS measurement. Because AS decomposes more slowly than bulk necromass and persists longer in soil, the ratio of AS to microbial necromass should exceed the AS to biomass ratio in living microbes. However, current conversion factors are derived from microbial biomass data, potentially leading to overestimation of MNC in soils. Here we propose a novel approach to refine AS‐based conversion factors for more accurate MNC estimation. Using biocrust soils as an ideal model system with minimal plant inputs, we derived MNC values by subtracting microbial biomass carbon from SOC. Our method directly quantified ratios of AS to MNC in soils and reduced the overestimation of MNC observed when using conventional biomass‐derived conversion factors in biocrust systems. Additionally, results from other ecosystem types suggested the potential of using biocrust‐derived ratios of AS to MNC in other soil types. This refined quantification approach enhances our understanding of SOC sequestration dynamics and provides more accurate parameters for modeling soil carbon cycling processes.

Biogeographic Patterns of Soil Microbial Biomass in Alpine Ecosystems Depend on Local Rather Than Regional Drivers - Kunwei Wang; Xiangjin Shen; Decai Gao; Jonas J. Lembrechts; Mai‐He Li; Beat Frey; Hang Yin; Hongli Pan; Jin Li; Xu Su; Wei Wang; Xiangtao Wang; et al. (Global Ecology and Biogeography, 2025)
Aim Conflicting distribution patterns of soil microbes along the elevation gradient in alpine ecosystems have been suggested based on observations from individual mountains. There remains a lack of biogeographical studies spanning multiple latitudes and climate zones, a scale appropriate to reveal general ecological patterns of soil microbial biomass (SMB) for alpine ecosystems. We conducted a large‐scale sampling campaign along elevational gradients in seven mountains across mainland China and investigated the biogeographical patterns of soil microorganisms and quantified the influencing environmental factors. Location China. Time Period 2019. Major Taxa Studied Seed plant species and soil microorganisms. Methods We sampled aboveground plants and belowground soils along elevational gradients from closed forests located below the alpine treeline up to the upper elevational limit of vegetation in seven mountains. We analysed the distribution patterns of SMB and the ratio of fungi to bacteria (F/B) and quantified four types of environmental factors at local (i.e., plant functional traits, soil physicochemical properties, and topography) and regional (i.e., macroclimate) scales to determine the drivers of microbial biomass in alpine ecosystems. Results We observed a hump‐shaped pattern of SMB along the elevation gradients, with a maximum near the alpine treeline. The soil nutrient status and plant functional traits played the most decisive roles in shaping SMB. Local‐scale environmental factors were more important than regional factors in determining SMB in alpine ecosystems. Main Conclusions Our study suggests that distribution patterns of SMB in alpine ecosystems are closely related to environmental heterogeneity rather than elevation alone. In the context of future temperature rises with global change, soil microbes can more easily track localised changes in microhabitats compared with top‐down effects of macroclimate, indicating that effects of climate warming on soil microbes could possibly be buffered by local environmental factors in alpine ecosystems.

Cascading Effects Within Soil Food Web Amplify Fungal Biomass and Necromass Production - Shixiu Zhang; Yakov Kuzyakov; Zhongjun Jia; Edith Bai; Elly Morriën; Aizhen Liang (Global Change Biology, 2025)
Soil food webs regulate microbial biomass and necromass production and are therefore critical for carbon sequestration. The mechanisms by which top predators regulate microbial necromass formation across multitrophic levels in the real‐world soil food web remain nearly unknown. This study investigates how top‐down forces—from omnivorous‐predaceous nematodes to microbivorous nematodes and microbes—affect the formation of microbial necromass within tritrophic food webs under contrasting tillage regimes (tillage (till) vs. no‐tillage (no‐till)) on black soils (Mollisols), using a 1‐year 13 C‐labeled straw in situ tracing experiment integrated with a long‐term (> 5 years) tillage trial. The fungal‐to‐bacterial necromass ratio increased strongly in the no‐till soil compared to the till soil, with omnivores‐predators being the key factor for these changes. In the no‐till soil, abundant and diverse omnivores‐predators (46% and 67% higher in abundance and richness than in the till soil) created a typical predator–prey relationship with fungivores. This relationship was characterized by heavy predation on fungivores (51% of omnivore‐predator diet) and opposite 1‐year dynamics of 13 C content between omnivores‐predators and fungivores. Such a predator–prey relationship substantially reduced fungivore activity (73% and 90% decrease in 13 C content and enrichment rate), while accompanied by increased fungal activity (64% and 50% increase in 13 C content and enrichment rate) in the no‐till soil compared to the till soil. This predator‐driven cascade down the food chain amplified the fungal contribution to the fungal‐to‐bacterial necromass ratio. Conversely, these interactions, disrupted by continuous tillage, weakened fungal functions by interrupting the trophic cascade. In conclusion, these tiny yet ubiquitous omnivorous‐predaceous nematodes exert a disproportionate impact on necromass formation by boosting fungal biomass and activity. Further manipulative experiments targeting multi‐trophic interactions are essential to disentangle the mechanisms of microbial necromass formation, given the inherent complexity of soil food webs and the observational nature of this study.

Effects of DOM Chemodiversity on Microbial Diversity in Forest Soils on a Continental Scale - Jian Wang; Lingrui Qu; Helena Osterholz; Yulin Qi; Xiangfeng Zeng; Edith Bai; Chao Wang (Global Change Biology, 2025)
Soil dissolved organic matter (DOM) is a critical reservoir of carbon and nutrients in forest ecosystems, playing a central role in carbon cycling and microbial community dynamics. However, the influence of DOM molecular‐level diversity (chemodiversity) on microbial community diversity and spatial distribution remains poorly understood. In this study, we used Fourier transform ion cyclotron resonance mass spectrometry and high‐throughput sequencing to analyze soil DOM and microbial diversity along a ~4,000 km forest transect in China. We found that soil DOM chemodiversity varies significantly across sites, initially increasing and then decreasing with latitude. Additionally, we observed that the biogeographic distribution of DOM components has differential effects on bacterial and fungal diversity: lipid‐like compounds are strongly associated with bacterial diversity, while aromatic‐, carbohydrate‐, and lipid‐like compounds primarily influence fungal diversity. Linear models and structural equation modeling both reveal that DOM acts as a key intermediary, mediating the effects of temperature and soil properties on microbial spatial distribution. Our findings emphasize the importance of DOM molecular characteristics in shaping microbial community structure and functioning, providing new insights into how environmental factors influence microbial ecosystems and soil carbon cycles in forest ecosystems.

Temperature effects on microbial carbon use efficiency and priming effects in soils under vegetation restoration - Jingyi Yang; Zitong Wang; Qing Chang; Ziping Liu; Qian Jiang; Xianlei Fan; Di Meng; Edith Bai (CATENA, 2025)

Nitrogen addition accelerates aboveground biomass sequestration in old-growth forests by stimulating ectomycorrhizal tree growth - Zhichun Yang; Zikun Mao; Wenwen Ji; Antonio Gazol; Shufang Liu; Chao Wang; Ji Ye; Fei Lin; Xugao Wang; Zhanqing Hao; Edith Bai; Zuoqiang Yuan (Journal of Environmental Management, 2025)

Soil Organic Carbon Increases With Decreasing Microbial Carbon Use Efficiency During Vegetation Restoration - Jingwei Shi; Lei Deng; Jianzhao Wu; Edith Bai; Ji Chen; Zhouping Shangguan; Yakov Kuzyakov (Global Change Biology, 2024)
Microbial carbon (C) use efficiency (CUE) describes the proportion of organic C used by microorganisms for anabolic processes, which increases with soil organic C (SOC) content on a global scale. However, it is unclear whether a similar relationship exists during natural vegetation restoration in terrestrial ecosystems. Here, we investigated the patterns of CUE along a 160‐year vegetation restoration chronosequence (from farmland to climax forest) estimated by stoichiometric modeling; additionally, we examined the relationship between CUE and SOC content and combined these results with a meta‐analysis. The combination indicated that vegetation restoration decreased CUE from 0.35 to 0.28. Surprisingly, SOC content increased with decreasing CUE during vegetation restoration because forest soils have low pH values and high microbial phosphorus limitations compared to early ecosystems, implying that climax forests may not sequester as much soil C as expected. The shift in soil pH was the most important predictor of CUE compared to climate, plant, and microbial factors. CUE changes were directly induced by soil pH and not by the pH‐induced microbial community. Alkaline soil acidification tended to decrease CUE. This first large‐scale estimate of the relationship between CUE and SOC during natural restoration highlights the need to strengthen C sink management in mature forests to sustain their C sequestration potential.

Differential contribution of microbial and plant-derived organic matter to soil organic carbon sequestration over two decades of natural revegetation and cropping - Hongling Qin; Yi Liu; Chunlan Chen; Anlei Chen; Yuting Liang; Carolyn R. Cornell; Xue Guo; Edith Bai; Haijun Hou; Dou Wang; Leyan Zhang; Jingyuan Wang; et al. (Science of The Total Environment, 2024)

Microbial and hydrothermal dolomite formation in Early Cretaceous lacustrine sediments in Yin'e Basin: Insights from petrology and geochemistry - Kun Zhang; Ziping Liu; Zhitao Xu; Qing Chang; Douaa Fathy; Rong Liu; Edith Bai (Sedimentary Geology, 2024)

Fabrication of black phosphorus/CdS heterostructure with enhancement photocatalytic degradation activity for tetrabromobisphenol A and toxicity prediction of intermediates - Zhaocheng Zhang; Dongyang He; Yangjian Zhou; Edith Bai; Jiao Qu; Ya-nan Zhang (Environmental Research, 2024)

Exogenous carbon addition soil mediated phosphorus dynamics under eight years continuous input of swine manure in a wheat-rice rotation - Chunlong Zhang; Xiaoyan Tang; Changquang Wang; Edith le Cadre; Rong Huang; Qi Tao; Yingjie Wu; Youlin Luo; Qiang Xu; Genchuan Bai; Bing Li (Agriculture, Ecosystems & Environment, 2024)

China's vegetation restoration programs accelerated vegetation greening on the Loess Plateau - Xianlei Fan; Ying Qu; Jing Zhang; Edith Bai (Agricultural and Forest Meteorology, 2024)

Drying-rewetting events enhance the priming effect on soil organic matter mineralization by maize straw addition - Hui Wang; Decai Gao; Guoqing Hu; Wenhua Xu; Yuping Zhuge; Edith Bai (CATENA, 2024)

Global prediction of soil microbial growth rates and carbon use efficiency based on the metabolic theory of ecology - Decai Gao; Edith Bai; Daniel Wasner; Frank Hagedorn (Soil Biology and Biochemistry, 2024)

Beyond conventional farming: exploring the benefits of planting basins with manure on soil quality as reflected in labile organic carbon and nitrogen indicators in Kenya - Edith Kichamu-Wachira; Yifan Bai; Zhihong Xu; Kathryn Reardon-Smith; Hongdou Liu; Duan Biggs (Journal of Soils and Sediments, 2024)
Purpose Soil quality is critical for plant growth and ecosystem sustainability. Understanding the indicators that indicate soil quality is, therefore, crucial. Labile organic carbon (C) and nitrogen (N) are important components of soil functions that impact productivity and environmental stability. This study aimed to explore the sensitivity of different labile C and N fractions, including water extractable organic C (WEOC) and total N (WEON) and hot water extractable organic C (HWEOC) and total N (HWEON), to planting basins with manure compared to conventional farming practices. Methods and methods Soil samples were drawn from 0–10 and 10–20 cm soil depths at 12 sites in Makueni County, Kenya. Samples were analysed for differences in WEOC, HWEOC, WEON, and HWEON between planting basins with manure and conventional farmer practices. We also assessed the correlations of the different labile C and N pools with other soil chemical properties linked to soil quality. Results and discussions The results showed that planting basins with manure significantly increased mean WEOC (171.53 µg g −1 ), HWEOC (353.62 µg g −1 ), WEON (26.60 µg g −1 ), and HWEON (26.39 µg g −1 ) compared to those of conventional farming practices ( p < 0.05 ). WEOC was positively correlated with WEON and δ 15 N ( p < 0.001 ) at the 0–10 cm soil layer suggesting that extractable organic matter can be used as an index for soil health and nutrient content. Conclusion The findings suggest that cold water and hot water extractable C and N are sensitive indicators of the effects of different land management practices on soil quality. The results further demonstrate that planting basins with manure can improve soil quality by increasing labile C and N pools.

Mineral composition controls the stabilization of microbially derived carbon and nitrogen in soils: Insights from an isotope tracing model - Xu Wang; Chao Wang; Xianlei Fan; Lifei Sun; Changpeng Sang; Xugao Wang; Ping Jiang; Yunting Fang; Edith Bai (Global Change Biology, 2024)
Evidence is emerging that microbial products and residues (necromass) contribute greatly to stable soil organic matter (SOM), which calls for the necessity of separating the microbial necromass from other SOM pools in models. However, the understanding on how microbial necromass stabilizes in soil, especially the mineral protection mechanisms, is still lacking. Here, we incubated 13 C‐ and 15 N‐labelled microbial necromass in a series of artificial soils varying in clay minerals and metal oxides. We found the mineralization, adsorption and desorption rate constants of necromass nitrogen were higher than those of necromass carbon. The accumulation rates of necromass carbon and nitrogen in mineral‐associated SOM were positively correlated with the specific surface area of clay minerals. Our results provide direct evidence for the protection role of mineral in microbial necromass stabilization and provide a platform for simulating microbial necromass separately in SOM models.

Ectomycorrhizal trees rely on nitrogen resorption less than arbuscular mycorrhizal trees globally - Bai Liu; Xianlei Fan; Di Meng; Ziping Liu; Decai Gao; Qing Chang; Edith Bai (Ecology Letters, 2024)
Nitrogen (N) resorption is an important pathway of N conservation, contributing to an important proportion of plant N requirement. However, whether the ratio of N resorption to N requirement may be affected by environmental factors, mycorrhizal types or atmospheric CO 2 concentration remains unclear. Here, we conducted a meta‐analysis on the impacts of environmental factors and mycorrhizal types on this ratio. We found this ratio in ectomycorrhizal (EM) trees decreased with mean annual precipitation, mean annual temperature, soil total N content and atmospheric CO 2 concentration and was significantly lower than that in arbuscular mycorrhizal (AM) trees. An in situ 15 N tracing experiment further confirmed that AM trees have a stronger reliance on N resorption than EM trees. Our study suggests that AM and EM trees potentially have different strategies for alleviation of progressive N limitation, highlighting the necessity of incorporating plant mycorrhizal types into Earth System Models.

Erosion effects on soil microbial carbon use efficiency in the mollisol cropland in northeast China - Xuebing Zhang; Guangting Pei; Tianyu Zhang; Xianlei Fan; Ziping Liu; Edith Bai (Soil Ecology Letters, 2023)

Comparison of carbon and nitrogen accumulation rate between bog and fen phases in a pristine peatland with the fen‐bog transition - Qiannan Yang; Ziping Liu; Edith Bai (Global Change Biology, 2023)
Long‐term carbon and nitrogen dynamics in peatlands are affected by both vegetation production and decomposition processes. Here, we examined the carbon accumulation rate (CAR), nitrogen accumulation rate (NAR) and δ 13 C, δ 15 N of plant residuals in a peat core dated back to ~8500 cal year BP in a temperate peatland in Northeast China. Impacted by the tephra during 1160 and 789 cal year BP and climate change, the peatland changed from a fen dominated by vascular plants to a bog dominated by Sphagnum mosses. We used the Clymo model to quantify peat addition rate and decay constant for acrotelm and catotelm layers during both bog and fen phases. Our studied peatland was dominated by Sphagnum fuscum during the bog phase (789 to −59 cal year BP) and lower accumulation rates in the acrotelm layer was found during this phase, suggesting the dominant role of volcanic eruption in the CAR of the peat core. Both mean CAR and NAR were higher during the bog phase than during the fen phase in our study, consistent with the results of the only one similar study in the literature. Because the input rate of organic matter was considered to be lower during the bog phase, the decomposition process must have been much lower during the bog phase than during the fen phase and potentially controlled CAR and NAR. During the fen phase, CAR was also lower under higher temperature and summer insolation, conditions beneficial for decomposition. δ 15 N of Sphagnum hinted that nitrogen fixation had a positive effect on nitrogen accumulation, particular in recent decades. Our study suggested that decomposition is more important for carbon and nitrogen sequestration than production in peatlands in most conditions and if future climate changes or human disturbance increase decomposition rate, carbon sequestration in peatlands will be jeopardized.

Corrigendum to “Context-dependency of tree species diversity, trait composition and stand structural attributes regulate temperate forest multifunctionality” [Sci. Total Environ., 757 (2021), 143724] - Anvar Sanaei; Arshad Ali; Zuoqiang Yuan; Shufang Liu; Fei Lin; Shuai Fang; Ji Ye; Zhanqing Hao; Michel Loreau; Edith Bai; Xugao Wang (Science of The Total Environment, 2023)

Biome responses to a hydroclimatic crisis in an Early Cretaceous (Barremian–Aptian) subtropical inland lake ecosystem, Northwest China - Kun Zhang; Rong Liu; Edith Bai; Zibin Zhao; Giovan Peyrotty; Douaa Fathy; Qing Chang; Ziping Liu; Kai Yang; Chuan Xu; Zhaojun Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Isotopic evidence for increased carbon and nitrogen exchanges between peatland plants and their symbiotic microbes with rising atmospheric CO 2 concentrations since 15,000 cal. year BP - Qiannan Yang; Ziping Liu; Benjamin Z. Houlton; Decai Gao; Qing Chang; Hongkai Li; Xianlei Fan; Bai Liu; Edith Bai (Global Change Biology, 2023)
Whether nitrogen (N) availability will limit plant growth and removal of atmospheric CO 2 by the terrestrial biosphere this century is controversial. Studies have suggested that N could progressively limit plant growth, as trees and soils accumulate N in slowly cycling biomass pools in response to increases in carbon sequestration. However, a question remains over whether longer‐term (decadal to century) feedbacks between climate, CO 2 and plant N uptake could emerge to reduce ecosystem‐level N limitations. The symbioses between plants and microbes can help plants to acquire N from the soil or from the atmosphere via biological N 2 fixation—the pathway through which N can be rapidly brought into ecosystems and thereby partially or completely alleviate N limitation on plant productivity. Here we present measurements of plant N isotope composition (δ 15 N) in a peat core that dates to 15,000 cal. year BP to ascertain ecosystem‐level N cycling responses to rising atmospheric CO 2 concentrations. We find that pre‐industrial increases in global atmospheric CO 2 concentrations corresponded with a decrease in the δ 15 N of both Sphagnum moss and Ericaceae when constrained for climatic factors. A modern experiment demonstrates that the δ 15 N of Sphagnum decreases with increasing N 2 ‐fixation rates. These findings suggest that plant‐microbe symbioses that facilitate N acquisition are, over the long term, enhanced under rising atmospheric CO 2 concentrations, highlighting an ecosystem‐level feedback mechanism whereby N constraints on terrestrial carbon storage can be overcome.

Three‐dimensional mapping of carbon, nitrogen, and phosphorus in soil microbial biomass and their stoichiometry at the global scale - Decai Gao; Edith Bai; Siyu Wang; Shengwei Zong; Ziping Liu; Xianlei Fan; Chunhong Zhao; Frank Hagedorn (Global Change Biology, 2022)
Soil microbial biomass and microbial stoichiometric ratios are important for understanding carbon and nutrient cycling in terrestrial ecosystems. Here, we compiled data from 12245 observations of soil microbial biomass from 1626 published studies to map global patterns of microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), microbial biomass phosphorus (MBP), and their stoichiometry using a random forest model. Concentrations of MBC, MBN, and MBP were most closely linked to soil organic carbon, while climatic factors were most important for stoichiometry in microbial biomass ratios. Modeled seasonal MBC concentrations peaked in summer in tundra and in boreal forests, but in autumn in subtropical and in tropical biomes. The global mean MBC/MBN, MBC/MBP, and MBN/MBP ratios were estimated to be 10, 48, and 6.7, respectively, at 0–30 cm soil depth. The highest concentrations, stocks, and microbial C/N/P ratios were found at high latitudes in tundra and boreal forests, probably due to the higher soil organic matter content, greater fungal abundance, and lower nutrient availability in colder than in warmer biomes. At 30–100 cm soil depth, concentrations of MBC, MBN, and MBP were highest in temperate forests. The MBC/MBP ratio showed greater flexibility at the global scale than did the MBC/MBN ratio, possibly reflecting physiological adaptations and microbial community shifts with latitude. The results of this study are important for understanding C, N, and P cycling at the global scale, as well as for developing soil C‐cycling models including soil microbial C, N, and P as important parameters.

An Optical Sensing Platform for Beta-Glucosidase Activity Using Protein-Inorganic Hybrid Nanoflowers - Ziping Liu; Shasha Liu; Decai Gao; Yanan Li; Ye Tian; Edith Bai (Journal of Fluorescence, 2022)

Long-term impact of prescribed burning on water use efficiency, biological nitrogen fixation, and tree growth of understory acacia species in a suburban forest ecosystem of subtropical Australia - Sabah Taresh; Shahla Hosseini Bai; Kadum Mohammed Abdullah; Jacinta Zalucki; Ashrafun Nessa; Negar Omidvar; Dianjie Wang; Juan Zhan; Fang Wang; Jiaping Yang; Edith Kichamu-Wachira; Zhihong Xu (Journal of Soils and Sediments, 2021)

Drought alters the carbon footprint of trees in soils—tracking the spatio‐temporal fate of 13 C‐labelled assimilates in the soil of an old‐growth pine forest - Decai Gao; Jobin Joseph; Roland A Werner; Ivano Brunner; Alois Zürcher; Christian Hug; Ao Wang; Chunhong Zhao; Edith Bai; Katrin Meusburger; Arthur Gessler; Frank Hagedorn (Global Change Biology, 2021)
Above and belowground compartments in ecosystems are closely coupled on daily to annual timescales. In mature forests, this interlinkage and how it is impacted by drought is still poorly understood. Here, we pulse‐labelled 100‐year‐old trees with 13 CO 2 within a 15‐year‐long irrigation experiment in a naturally dry pine forest to quantify how drought regime affects the transfer and use of assimilates from trees to the rhizosphere and associated microbial communities. It took 4 days until new 13 C‐labelled assimilates were allocated to the rhizosphere. One year later, the 13 C signal of the 3‐h long pulse labelling was still detectable in stem and soil respiration, which provides evidence that parts of the assimilates are stored in trees before they are used for metabolic processes in the rhizosphere. Irrigation removing the natural water stress reduced the mean C residence time from canopy uptake until soil respiration from 89 to 40 days. Moreover, irrigation increased the amount of assimilates transferred to and respired in the soil within the first 10 days by 370%. A small precipitation event rewetting surface soils altered this pattern rapidly and reduced the effect size to +35%. Microbial biomass incorporated 46 ± 5% and 31 ± 7% of the C used in the rhizosphere in the dry control and irrigation treatment respectively. Mapping the spatial distribution of soil‐respired 13 CO 2 around the 10 pulse‐labelled trees showed that tree rhizospheres extended laterally 2.8 times beyond tree canopies, implying that there is a strong overlap of the rhizosphere among adjacent trees. Irrigation increased the rhizosphere area by 60%, which gives evidence of a long‐term acclimation of trees and their rhizosphere to the drought regime. The moisture‐sensitive transfer and use of C in the rhizosphere has consequences for C allocation within trees, soil microbial communities and soil carbon storage.

Large‐scale importance of microbial carbon use efficiency and necromass to soil organic carbon - Chao Wang; Lingrui Qu; Liuming Yang; Dongwei Liu; Ember Morrissey; Renhui Miao; Ziping Liu; Qingkui Wang; Yunting Fang; Edith Bai (Global Change Biology, 2021)
Optimal methods for incorporating soil microbial mechanisms of carbon (C) cycling into Earth system models (ESMs) are still under debate. Specifically, whether soil microbial physiology parameters and residual materials are important to soil organic C (SOC) content is still unclear. Here, we explored the effects of biotic and abiotic factors on SOC content based on a survey of soils from 16 locations along a ~4000 km forest transect in eastern China, spanning a wide range of climate, soil conditions, and microbial communities. We found that SOC was highly correlated with soil microbial biomass C (MBC) and amino sugar (AS) concentration, an index of microbial necromass. Microbial C use efficiency (CUE) was significantly related to the variations in SOC along this national‐scale transect. Furthermore, the effect of climatic and edaphic factors on SOC was mainly via their regulation on microbial physiological properties (CUE and MBC). We also found that regression models on explanation of SOC variations with microbial physiological parameters and AS performed better than the models without them. Our results provide the empirical linkages among climate, microbial characteristics, and SOC content at large scale and confirm the necessity of incorporating microbial biomass and necromass pools in ESMs under global change scenarios.

Elevated temperature increases the accumulation of microbial necromass nitrogen in soil via increasing microbial turnover - Xu Wang; Chao Wang; M. Francesca Cotrufo; Lifei Sun; Ping Jiang; Ziping Liu; Edith Bai (Global Change Biology, 2020)
Microbial‐derived nitrogen (N) is now recognized as an important source of soil organic N. However, the mechanisms that govern the production of microbial necromass N, its turnover, and stabilization in soil remain poorly understood. To assess the effects of elevated temperature on bacterial and fungal necromass N production, turnover, and stabilization, we incubated 15 N‐labeled bacterial and fungal necromass under optimum moisture conditions at 10°C, 15°C, and 25°C. We developed a new 15 N tracing model to calculate the production and mineralization rates of necromass N. Our results showed that bacterial and fungal necromass N had similar mineralization rates, despite their contrasting chemistry. Most bacterial and fungal necromass 15 N was recovered in the mineral‐associated organic matter fraction through microbial anabolism, suggesting that mineral association plays an important role in stabilizing necromass N in soil, independently of necromass chemistry. Elevated temperature significantly increased the accumulation of necromass N in soil, due to the relatively higher microbial turnover and production of necromass N with increasing temperature than the increases in microbial necromass N mineralization. In conclusion, we found elevated temperature may increase the contribution of microbial necromass N to mineral‐stabilized soil organic N.

The strategy of microbial utilization of the deposited N in a temperate forest soil - Wei Zhang; Xiaochen Zhang; Edith Bai; Yanhe Cui; Hongbo He; Xudong Zhang (Biology and Fertility of Soils, 2020)

Predicting plant–soil N cycling and soil N2O emissions in a Chinese old-growth temperate forest under global changes: uncertainty and implications - Weiwei Dai; Edith Bai; Wei Li; Ping Jiang; Guanhua Dai; Xingbo Zheng (Soil Ecology Letters, 2020)

Soil resource status affects the responses of nitrogen processes to changes in temperature and moisture - Lifei Sun; Zongwei Xia; Changpeng Sang; Xu Wang; Bo Peng; Chao Wang; Jinbo Zhang; Christoph Müller; Edith Bai (Biology and Fertility of Soils, 2019)

Responses of terrestrial nitrogen pools and dynamics to different patterns of freeze‐thaw cycle: A meta‐analysis - Decai Gao; Lei Zhang; Jun Liu; Bo Peng; Zhenzhen Fan; Weiwei Dai; Ping Jiang; Edith Bai (Global Change Biology, 2018)
Altered freeze‐thaw cycle ( FTC ) patterns due to global climate change may affect nitrogen (N) cycling in terrestrial ecosystems. However, the general responses of soil N pools and fluxes to different FTC patterns are still poorly understood. Here, we compiled data of 1519 observations from 63 studies and conducted a meta‐analysis of the responses of 17 variables involved in terrestrial N pools and fluxes to FTC . Results showed that under FTC treatment, soil NH 4 + , NO 3 − , NO 3 − leaching, and N 2 O emission significantly increased by 18.5%, 18.3%, 66.9%, and 144.9%, respectively; and soil total N ( TN ) and microbial biomass N ( MBN ) significantly decreased by 26.2% and 4.7%, respectively; while net N mineralization or nitrification rates did not change. Temperate and cropland ecosystems with relatively high soil nutrient contents were more responsive to FTC than alpine and arctic tundra ecosystems with rapid microbial acclimation. Therefore, altered FTC patterns (such as increased duration of FTC , temperature of freeze, amplitude of freeze, and frequency of FTC ) due to global climate warming would enhance the release of inorganic N and the losses of N via leaching and N 2 O emissions. Results of this meta‐analysis help better understand the responses of N cycling to FTC and the relationships between FTC patterns and N pools and N fluxes.

Ten years of elevated CO2 affects soil greenhouse gas fluxes in an open top chamber experiment - Jianfei Sun; Zongwei Xia; Tongxin He; Weiwei Dai; Bo Peng; Jun Liu; Decai Gao; Ping Jiang; Shijie Han; Edith Bai (Plant and Soil, 2017)

Depth profiles of soil carbon isotopes along a semi-arid grassland transect in northern China - Chao Wang; Haiwei Wei; Dongwei Liu; Wentao Luo; Jianfeng Hou; Weixin Cheng; Xingguo Han; Edith Bai (Plant and Soil, 2017)

Different fates of deposited and in a temperate forest in northeast China: a 15 N tracer study - Jun Liu; Bo Peng; Zongwei Xia; Jianfei Sun; Decai Gao; Weiwei Dai; Ping Jiang; Edith Bai (Global Change Biology, 2017)
Increasing atmospheric reactive nitrogen (N) deposition due to human activities could change N cycling in terrestrial ecosystems. However, the differences between the fates of deposited and are still not fully understood. Here, we investigated the fates of deposited and , respectively, via the application of 15 NH 4 NO 3 and NH 4 15 NO 3 in a temperate forest ecosystem. Results showed that at 410 days after tracer application, most was immobilized in litter layer (50 ± 2%), while a considerable amount of penetrated into 0–5 cm mineral soil (42 ± 2%), indicating that litter layer and 0–5 cm mineral soil were the major N sinks of and , respectively. Broad‐leaved trees assimilated more 15 N under NH 4 15 NO 3 treatment compared to under 15 NH 4 NO 3 treatment, indicating their preference for –N. At 410 days after tracer application, 16 ± 4% added 15 N was found in aboveground biomass under treatment, which was twice more than that under treatment (6 ± 1%). At the same time, approximately 80% added 15 N was recovered in soil and plants under both treatments, which suggested that this forest had high potential for retention of deposited N. These results provided evidence that there were great differences between the fates of deposited and , which could help us better understand the mechanisms and capability of forest ecosystems as a sink of reactive nitrogen.

Effect of nitrogen addition on the variations in the natural abundance of nitrogen isotopes of plant and soil components - Jun Liu; Chao Wang; Bo Peng; Zongwei Xia; Ping Jiang; Edith Bai (Plant and Soil, 2017)

Thresholds in decoupled soil-plant elements under changing climatic conditions - Wentao Luo; Jordi Sardans; Feike A. Dijkstra; Josep Peñuelas; Xiao-Tao Lü; Honghui Wu; Mai-He Li; Edith Bai; Zhengwen Wang; Xingguo Han; Yong Jiang (Plant and Soil, 2016)

Local-scale determinants of elemental stoichiometry of soil in an old-growth temperate forest - Yanyan Suo; Zuoqiang Yuan; Fei Lin; Xugao Wang; Ji Ye; Edith Bai; Zhanqing Hao (Plant and Soil, 2016)

Nitrogen addition affects chemical compositions of plant tissues, litter and soil organic matter - Jun Liu; Nana Wu; Hui Wang; Jianfei Sun; Bo Peng; Ping Jiang; Edith Bai (Ecology, 2016)
Increasing nitrogen (N) deposition or fertilization has been found to significantly affect carbon (C) cycling. However, a comprehensive understanding of how different C chemical components of plant, litter, and soil would respond to external N addition is still lacking. We compiled data of 1,160 observations from 52 individual studies and conducted a meta‐analysis of N addition effects on 18 variables related to C chemical compositions in terrestrial ecosystems. Results showed that plant lignin (+7.13%), plant protein (+25.94%), and soil lignin (+7.30%) were significantly increased by N addition, and plant hemicellulose (−4.39%) was significantly decreased, whereas plant fiber, plant cellulose, plant non‐structural carbohydrate ( NSC ), litter lignin, and litter cellulose were not significantly changed. The effects of N addition on C chemical composition varied among different ecosystems/plant types and different forms of N addition. Increasing treatment duration did not significantly change the effects of N addition on the chemical composition of plant, litter, and soil C. With increasing N addition rate, the effect of N addition on plant lignin, plant fiber, plant cellulose, and plant protein increased, while the effect of N addition on plant hemicellulose, plant NSC , and litter cellulose became more negative. Our meta‐analysis provided a systematic evaluation of the responses of different C chemical components to N addition in the plant–litter–soil continuum. Results suggest that the change of plant and soil C chemical composition under N addition may be beneficial for ecosystem C sequestration and could affect ecosystem structure and function in the future.

The priming effect of soluble carbon inputs in organic and mineral soils from a temperate forest - Hui Wang; Wenhua Xu; Guoqing Hu; Weiwei Dai; Ping Jiang; Edith Bai (Oecologia, 2015)

Nitrogen deposition weakens plant–microbe interactions in grassland ecosystems - Cunzheng Wei; Qiang Yu; Edith Bai; Xiaotao Lü; Qi Li; Jianyang Xia; Paul Kardol; Wenju Liang; Zhengwen Wang; Xingguo Han (Global Change Biology, 2013)
Soil carbon (C) and nitrogen (N) stoichiometry is a main driver of ecosystem functioning. Global N enrichment has greatly changed soil C : N ratios, but how altered resource stoichiometry influences the complexity of direct and indirect interactions among plants, soils, and microbial communities has rarely been explored. Here, we investigated the responses of the plant‐soil‐microbe system to multi‐level N additions and the role of dissolved organic carbon ( DOC ) and inorganic N stoichiometry in regulating microbial biomass in semiarid grassland in northern China. We documented a significant positive correlation between DOC and inorganic N across the N addition gradient, which contradicts the negative nonlinear correlation between nitrate accrual and DOC availability commonly observed in natural ecosystems. Using hierarchical structural equation modeling, we found that soil acidification resulting from N addition, rather than changes in the plant community, was most closely related to shifts in soil microbial community composition and decline of microbial respiration. These findings indicate a down‐regulating effect of high N availability on plant–microbe interactions. That is, with the limiting factor for microbial biomass shifting from resource stoichiometry to soil acidity, N enrichment weakens the bottom‐up control of soil microorganisms by plant‐derived C sources. These results highlight the importance of integratively studying the plant‐soil‐microbe system in improving our understanding of ecosystem functioning under conditions of global N enrichment.

Spatial variation of the stable nitrogen isotope ratio of woody plants along a topoedaphic gradient in a subtropical savanna - Edith Bai; Thomas W. Boutton; Feng Liu; X. Ben Wu; Steven R. Archer; C. Thomas Hallmark (Oecologia, 2009)

Variation in woody plant δ13C along a topoedaphic gradient in a subtropical savanna parkland - Edith Bai; Thomas W. Boutton; Feng Liu; X. Ben Wu; Steven R. Archer (Oecologia, 2008)